A note on the conceptual design of polymeric composite automotive bumper system - Sapuan, S. M.; Maleque, Md. Abdul; Hameedullah, M.; Suddin, M.N.; Ismail , N. (Elsevier, 2005)
In this paper, a conceptual design approach to the development of polymeric-based composite automotive bumper system is presented. Various methods of creativity, such as mindmapping, product design specifications, brainstorming, morphology chart, analogy and weighted objective methods are employed for the development of composite bumper fascia and for the selection of materials for bumper system. The evaluation of conceptual design for bumper fascia is carried out using weighted objective method and highest utility value is appeared to be the best design concept. Polymer-based composites are the best materials for bumper fascia which are aesthetically pleasant, lighter weight and offer many more substantial advantages.